2019
DOI: 10.1080/21548455.2019.1584419
|View full text |Cite
|
Sign up to set email alerts
|

Family connections to local science issues: how scientists use questions to engage families in personally-relevant learning during science-themed workshops

Abstract: This study investigates how scientist-led educational programs, held in libraries, can make local science issues relevant to families. Given the need for an educated citizenry, it is important to explore if scientistsas learning facilitatorscan use educational strategies to engage intergenerational groups. We view family learning from a sociocultural perspective where parent-child interactions and sensemaking practices are the focus of our analysis. We analyzed three water quality-themed workshops held at publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
0
13
0
3
Order By: Relevance
“…A further issue of concern is the underrepresentation of women, ethnic minorities, and people from low socioeconomic backgrounds in STEM fields, limiting the pool from which highly skilled individuals can be drawn (Marginson et al, 2013). A lack of diverse representation in STEM fields is also problematic because it leads to a narrower range of perspectives that can contribute to solving problems and driving innovation (van den Hurk et al, 2019).…”
Section: Concerns With Stem Participation and Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…A further issue of concern is the underrepresentation of women, ethnic minorities, and people from low socioeconomic backgrounds in STEM fields, limiting the pool from which highly skilled individuals can be drawn (Marginson et al, 2013). A lack of diverse representation in STEM fields is also problematic because it leads to a narrower range of perspectives that can contribute to solving problems and driving innovation (van den Hurk et al, 2019).…”
Section: Concerns With Stem Participation and Educationmentioning
confidence: 99%
“…Examples of such strategies include increasing awareness of STEM careers, making STEM role models available to young people, challenging stereotypes, and building student self-efficacy in STEM (van Tuijl and van der Molen, 2016). At the school-level, pedagogical approaches that contextualize and personalize STEM learning, connect STEM learning with local communities, and integrate the teaching of content with thinking skills (such as critical and creative thinking, problem solving, and flexible thinking) are also positioned as strategies that can enhance student achievement and interest in STEM (Marginson et al, 2013). The idea of localized learning has roots in economic geography, where it has been noted that local conditions and spatial proximity between stakeholders positively influences the generation of skills, processes, and products (Malmberg and Maskell, 2006).…”
Section: Linking Stem Pedagogy With Local Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…One mother commented on this issue to one of the researchers saying: The need for better mediational means in informal environments (not only science museums) is the outcome of many studies. McClain and Zimmerman (2019) suggested that a more structured learning environment can support opportunities for conversations between family members to promote connections between the scientific phenomena in the learning environment and the family past shared experiences. Furthermore, Harris and Winterbottom (2018) showed how family learning can be developed during a facilitated workshop to spark scientific talk between family members and encourage an inquiry-based approach.…”
Section: Discussionmentioning
confidence: 99%
“…There is vast body of knowledge examining parent-child interactions in museums (Andre et al, 2017;Callanan et al, 2020;Degotardi et al, 2019;Harris & Winterbottom, 2018;McClain & Zimmerman, 2019;Taggart et al, 2020;Vandermaas-Peeler et al, 2016) and due to the fact that parents are among the most influential factors in children's learning, there is always the need to add to this body of knowledge. Informal science environments and exhibit designers who wish to promote science learning for children must carefully consider the role of parents in this learning process.…”
Section: Introductionmentioning
confidence: 99%